The structural model of the relationships between media exposure, family communication, peer pressure, cultural values and violent behaviour among adolescents - Eneizat, Mohammad Fawwaz Salman (2024)
Adolescent violence is one of the most decisive issues confronted by countries all around the globe. Presently, Jordan is facing a substantial raise in violent behaviour among adolescents. It is a complex fact that results from the interaction of several contributing risk factors e.g., exposure to violent media content, cultural practices, peer pressure, family, and school environment. Thus, the present study seeks to examine the relationship among media exposure, family communication, peer pressure, cultural values, and their influence on violent behaviour among adolescents. Additionally, the moderating effects of socioeconomic status (SES) and gender with violent behaviour among adolescents are also examined. The theoretical support of Social Learning Theory (SLT) and Cultivation Theory (CT) are taken to explain the phenomenon. The quantitative methodology was used to analyse the relationship between the proposed variables. Stratified random and simple random samplings are used to get data from 248 adolescents from 20 Jordanian schools. Partial Least Squares (PLS) and Structural Equation Modelling techniques were used to test the hypotheses. The results found that media exposure, family communication, peer pressure, and cultural values directly impacted violent behaviour among adolescents. The findings also revealed that gender moderates the relationship between cultural values and violent behaviour and that SES moderates the relationship between media exposure, peer pressure, and violent behaviour. The study suggests that people at the helm of affairs, stakeholders, and civil society should devise pragmatic policies to curb the menace of violent behaviour among adolescents in Jordan.